2003
DOI: 10.1667/0033-7587(2003)159[0361:porioc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Radiation-Induced Oral Cavity Mucositis by Plasmid/Liposome Delivery of the Human Manganese Superoxide Dismutase (SOD2) Transgene

Abstract: Oral cavity mucositis is a major toxicity of radiation therapy for head and neck cancer. In the present mouse model studies, we evaluated intraoral administration of SOD2-PL complexes 24 h before single-fraction 30-Gy irradiation for the prevention of oral cavity mucositis. Expression of the human SOD2 transgene in the oral cavity of C3H/HeNsd mice was demonstrated by nested reverse transcriptase polymerase chain reaction (RT-PCR). Mice treated intraorally with bacterial beta-galactosidase gene-plasmid/liposom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 23 publications
3
84
0
Order By: Relevance
“…In two model systems (lung and oral cavity), orthotopic tumors were not detectably protected from irradiation killing under conditions of normal tissue radiation protection. 21,52 Transient overexpression of MnSOD in tumor cell lines in vitro has been demonstrated to increase radiosensitivity, confirming studies by Oberley and co-workers 53,54 and documenting the intrinsic inability of squamous and adenocarcinoma cell lines to neutralize effectively hydrogen peroxide produced by dismutation of superoxide. 54 For effective translation of MnSOD-PL pulmonary radiation protection to clinical radiotherapy, its adaptation for use in fractionated radiotherapy using clinically relevant doses in the range of 180-210 cGy/day was felt to be essential.…”
Section: Lung Irradiation Protection By Inhalation Of Mnsod-pl M Carpsupporting
confidence: 76%
See 3 more Smart Citations
“…In two model systems (lung and oral cavity), orthotopic tumors were not detectably protected from irradiation killing under conditions of normal tissue radiation protection. 21,52 Transient overexpression of MnSOD in tumor cell lines in vitro has been demonstrated to increase radiosensitivity, confirming studies by Oberley and co-workers 53,54 and documenting the intrinsic inability of squamous and adenocarcinoma cell lines to neutralize effectively hydrogen peroxide produced by dismutation of superoxide. 54 For effective translation of MnSOD-PL pulmonary radiation protection to clinical radiotherapy, its adaptation for use in fractionated radiotherapy using clinically relevant doses in the range of 180-210 cGy/day was felt to be essential.…”
Section: Lung Irradiation Protection By Inhalation Of Mnsod-pl M Carpsupporting
confidence: 76%
“…51 However, by using a construct of the Cu/ZnSOD transgene to which was attached the mitochondrial localization signal of MnSOD, an effective transgene protein for radioprotection was demonstrated. 51 MnSOD-PL administration prior to irradiation of lung, 12 oral cavity, 21 esophagus, 17 bladder, 22 and intestine 23 has Lung irradiation protection by inhalation of MnSOD-PL M Carpenter et al been shown to provide radioprotection in each organ's target volume. In two model systems (lung and oral cavity), orthotopic tumors were not detectably protected from irradiation killing under conditions of normal tissue radiation protection.…”
Section: Lung Irradiation Protection By Inhalation Of Mnsod-pl M Carpmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in retinal pigment epithelial cells, the gene dosage of SOD2 directly relates to the degree of mitochondrial injury and apoptosis induced by H 2 O 2 (Kasahara et al, 2005). In hemopoietic cells, SOD2 transgene decreases ionizing radiation-induced mitochondrial membrane permeability, cytochrome c release and caspase-3 activation (Guo et al, 2003). Collectively, these data provide strong evidence that increased mitochondrial ROS in the presence of pro-oxidant stressors, including hyperglycemia, can be prevented by enhancing mitochondrial SOD2 activity.…”
Section: Discussionmentioning
confidence: 73%